Gray models for the prediction of results in track and field events - Jiang, Y.; Li, J.; Bao, H.; Wang, J.; Hua, F. (International Journal of Sports Science and Engineering, 2007)
Considering the result record of a sport event regarding years as a time serial, it can be described by a model of time serial including certain model and uncertain model. In this paper, we created the gray model GM(1, 1) as differential equation for track and field events based on gray system theory. Based on historical record data of Olympic Games, parameters of the equation are solved by using the method of least squares. The validation is down. And the comparison with other methods shows that the gray model it is accepted. It can be used to predict result of track and field events of 2008 Bejing Olympic Games, etc.